PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF BENAR SALAH BERANTAI TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 2 LINGGO SARI BAGANTI - Siska, Dona; Anggraini, Villia; Mardiyah, Ainil (STKIP PGRI Sumbar, 2013)
This research has background by students less activity and concept of students understanding in mathematical, also students teamwork in learning process. This research aims to know students activity and to know what is concept of students understanding in mathematic applying by students was wrong real correct strategy related has good effect than the concept of students understanding in mathematical with conventional study. This research was experiment, with research device of subject was random. The population was class students ofÂ VII SMPN 2 Linggo Sari Baganti. The samples were class of VIIb as experiment and VIId as control class. Instrument this research was final test concept of students understanding in mathematics. Test used in essay form with reliability of test r11 = 0,8955. Technique the data analysis was test by using MINITAB. Based on the value of final test mathematics at both classes of samples obtained by experiment class had mean score = 74,53, standard deviation = 20,11, control class had mean score = 54,14, standard deviation = 21,60. Result of data analysis known by both samples have homogeneous and normal distribution Î± = 0, 05, P-Value 0,000, so that can be concluded the concept of students understanding in mathematics by applying wrong real correct strategy related had good effect than the students understanding with conventional study at students of VII SMPN 2 Linggo Sari Baganti in academic year 2012/2013.